Comparison of Functional Status and Depression in Younger and Older Patients with Chronic Low Back Pain: A Multi-center Crosssectional Survey - Yumuşakhuylu, Yasemin; İçağasıoğlu, Afitap; Toraman, Naciye Füsun; Kaymak Karataş, Gülçin; Kuru, Ömer; Kirazlı, Yeşim; Çapacı, Kazım; Eriman, Esma; Haliloğlu, Sema; Ketenci, Ayşegül (Turkish journal of osteoporosis, 2024)
[LANGUAGE=”English”]Objective:This study compared the differences in functionality and depression between younger and older patients with chronic low back pain (CLBP).Materials and Methods:This multi-center cross-sectional survey enrolled subjects with CLBP who visited physical medicine and rehabilitation clinics in seven different regions of Turkey. Sociodemographic data were collected via questionnaires. Functional status was evaluated with Roland-Morris Disability index (RMDI), and psychological health was evaluated with Beck Depression inventory (BDI).Results:The sample included 106 younger [mean age: 24.3 (range: 18-30) years] and 104 older [mean age: 70.5 (range: 65-108) years] subjects. No significant difference was found in the gender distribution between the younger (38 males, 68 females) and older (38 males, 66 females) groups (p=0.917). The BDI was 11.90±10.6 in the younger subjects and 16.17±10.72 in the older subjects (p=0.002), whereas the mean RMDIs were 10.31±6.36 and 16.04±5.36, respectively (p=0.001).Conclusion:The loss of functional capacity and depression resulting from CLBP are serious threats to public health and are predictive of chronic disability. The development of social programs that address risk factors will reduce the risk of CLBP, improve quality of life, reduce workforce losses and contribute significantly to public health.[LANGUAGE=”Turkish”]ÖZETAmaç:Bu çalışmada genç ve yaşlı kronik bel ağrılı (KBA) hastaların fonksiyonellik ve depresyon açısından farklılıkları karşılaştırılmıştır.Gereç ve Yöntem:Bu çok merkezli kesitsel çalışmaya, Türkiye’nin 7 bölgesindeki farklı fiziksel tıp ve rehabilitasyon polikliniklerine başvuran KBA’lı 106 genç 104 yaşlı hasta dahil edilmiştir. Sosyodemografik veriler anketler yoluyla toplanmıştır. Fonksiyonel durum Roland-Morris Dizabilite anketi (RMDA) ile, psikolojik sorgulama ise Beck Depresyon anketi (BDA) ile değerlendirilmiştir. İstatistiksel analizler IBM SPSS Statistics 22 paket programıyla yapılmıştır.Bulgular:Çalışmamıza 106 genç [ortalama yaş: 24,3 (18-30)] ve 104 yaşlı [ortalama yaş: 70,5 (65-108)] hasta katıldı. Cinsiyet dağılımı açısından genç (68 kadın, 38 erkek) ve yaşlı hasta (66 kadın, 38 erkek) grupları arasında anlamlı bir farklılık yoktu (p=0,917). BDA sonuçları gençlerde 11,90±10,6 iken yaşlı hasta grubunda 16,17±10,72 bulunmuşken (p=0,002), RMDA ortalamaları geçlerde ve yaşlılarda sırasıyla 10,31±6,36 ve 16,04±5,36 olarak bulundu (p=0,001).Sonuç:KBA sık karşılaşılan, fonksiyonel ve psikolojik problemlere yol açtığı bilinen bir hastalıktır. Bel ağrısı kaynaklı fonksiyon kaybı ve depresyon ciddi halk sağlığı problem ve kronik dizabilitenin belirleyicilerindendir. KBA gelişimini engelleyecek risk faktörlerinin belirlenmesi ve buna yönelik sosyal programların geliştirilmesi, hassas kişilerde yaşam kalitesini artıracak, iş gücü kaybını azaltacak ve halk sağlığına önemli olumlu etkileri olacaktır.